Association between venous thromboembolism and iron-deficiency anemia. Issue 4 (June 2015) - Hung, Shih-Han; Lin, Herng-Ching; Chung, Shiu-Dong
<x xml:space="preserve">Abstract</x> Although iron-deficiency anemia (IDA) as a rare cause of cerebral sinus thrombosis was supported by several studies, the relationship between IDA and venous thromboembolisms (VTEs) remains unclear. In this study, we evaluated the association between IDA and subsequent VTEs based on a population-based coverage database. We retrieved data for this case–control study from the Taiwan Longitudinal Health Insurance Database 2000. In total, 2522 cases with VTE and 12 610 randomly selected controls were included. A conditional logistic regression was used to examine the association of VTEs with previously diagnosed IDA. The χ2 test indicated that there was a significant difference in the prevalence of prior IDA between subjects with a VTE and the controls (3.41 vs. 2.06%, respectively, P < 0.001). The conditional logistic regression analysis showed that the odds ratio (OR) of previous IDA for subjects with a VTE was 1.43 [95% confidence interval (CI): 1.10–1.87] compared with the controls after adjusting for monthly income, geographic region, urbanization level, cancer, inflammatory bowel disease, heart failure, hypertension, diabetes, coronary heart disease, hyperlipidemia, renal disease, obesity, and whether or not a subject was hospitalized and whether or not a subject had suffered from a fracture within 1 year prior to the index date. The adjusted OR for prior IDA in subjects with deep-vein thrombosis was 1.43 (95% CI: 1.08–1.90) compared with the controls. However, there was no significant difference in the adjusted OR of prior IDA between subjects with a pulmonary embolism and the controls (OR: 1.10; 95% CI: 0.63–1.92). We concluded that there was an association between IDA and VTEs.